Who to show the ad to? Behavioral targeting in Internet advertising. Issue 1 (21st March 2022) - Xiong, Wei; Xiong, Ziyi; Tian, Tina
Abstract : Purpose: The performance of behavioral targeting (BT) mainly relies on the effectiveness of user classification since advertisers always want to target their advertisements to the most relevant users. In this paper, the authors frame the BT as a user classification problem and describe a machine learning–based approach for solving it. Design/methodology/approach: To perform such a study, two major research questions are investigated: the first question is how to represent a user's online behavior. A good representation strategy should be able to effectively classify users based on their online activities. The second question is how different representation strategies affect the targeting performance. The authors propose three user behavior representation methods and compare them empirically using the area under the receiver operating characteristic curve (AUC) as a performance measure. Findings: The experimental results indicate that ad campaign effectiveness can be significantly improved by combining user search queries, clicked URLs and clicked ads as a user profile. In addition, the authors also explore the temporal aspect of user behavior history by investigating the effect of history length on targeting performance. The authors note that an improvement of approximately 6.5% in AUC is achieved when user history is extended from 1 day to 14 days, which is substantial in targeting performance. Originality/value: This paper confirms the effectiveness of BT on user classification and provides a validation of BT for Internet advertising.